Key Performance Indicators Applied in Medicine - Bento, Ricardo Ferreira; Gândara, Mara Edwirges Rocha; Penteado, Silvio Pires (International Archives of Otorhinolaryngology, 2025)
Key performance indicators (KPIs) measure the critical functions and activities that must be performed in an organization to provide management with an assessment of quantity and quality, from which it can aid strategic decisions to achieve objectives.To map the literature review on KPIs in the context of medicine.In the literature review, we adopted a proposed model and made appropriate adaptations to it. The PubMed database was chosen, with filters applied to define a path. The findings of the articles were briefly discussed in comparison with others to highlight specific findings.Almost 100 research articles were eligible for investigation in a wide range of third- and second-degree medical specialties. In these articles, the KPIs are numbered from 1 up to 797 qualitative and quantitative measures.The KPIs are not limited to a financial regime; instead, in the field of medicine, they play an important role in a wide range of medical specialties, from clinics, therapeutics, surgery, pharmacy, research, regulatory affairs, hospitalization, management, and product development. These indicators can be implemented and evaluated by different means, from simple resources such as home visit, telephone survey, cross-comparison with a benchmark, questionnaires, spreadsheets, to the most sophisticated technology, such as IT resources, artificial intelligence, the linear hinges model, the Research and Development/University of California, Los Angeles (RAND/UCLA) appropriateness method, and the Monte Carlo simulation.
Keywords: health care quality indicators; institutional management teams; quality improvements; health services research; knowledge discovery